KEDUDUKAN CUCU SEBAGAI AHLI WARIS PENGGANTI BERDASARKAN KETENTUAN KOMPILASI HUKUM ISLAM DAN PERSPEKTIF IMAM NAWAWI - Alfina Indah Putri Fina; Muhamad Arief Al Hakim (Sahaja: Journal Sharia and Humanities, 2024)
This article examines the position of grandchildren as substitute heirs in the Islamic inheritance law system, with a focus on the provisions in the Compilation of Islamic Law (KHI) and the perspective of Imam Nawawi. This research aims to identify how the position of grandchildren as successor heirs is regulated in the two legal sources and compare their suitability. The method used is a literature study with qualitative analysis of Islamic legal texts and the works of Imam Nawawi. The research results show that although the KHI regulates the position of grandchildren as substitute heirs under certain conditions, there are differences in the interpretation put forward by Imam Nawawi regarding this matter.